Baseline activity predicts working memory load of preceding task condition. Issue 11 (13th June 2012) - Pyka, Martin; Hahn, Tim; Heider, Dominik; Krug, Axel; Sommer, Jens; Kircher, Tilo; Jansen, Andreas
<x xml:space="preserve">Abstract</x> The conceptual notion of the so‐called resting state of the brain has been recently challenged by studies indicating a continuing effect of cognitive processes on subsequent rest. In particular, activity in posterior parietal and medial prefrontal areas has been found to be modulated by preceding experimental conditions. In this study, we investigated which brain areas show working memory dependent patterns in subsequent baseline periods and how specific they are for the preceding experimental condition. During functional magnetic resonance imaging, 94 subjects performed a letter‐version of the n‐back task with the conditions 0‐back and 2‐back followed by a low‐level baseline in which subjects had to passively observe the letters appearing. In a univariate analysis, 2‐back served as control condition while 0‐back, baseline after 0‐back and baseline after 2‐back were modeled as regressors to test for activity changes between both baseline conditions. Additionally, we tested, using Gaussian process classifiers, the recognition of task condition from functional images acquired during baseline. Besides the expected activity changes in the precuneus and medial prefrontal cortex, we found differential activity in the thalamus, putamen, and postcentral gyrus that were affected by the preceding task. The multivariate analysis revealed that images of the subsequent baseline block contain task related patterns that yield a recognition rate of 70%. The results suggest that the influence of a cognitive task on subsequent baseline is strong and specific for some areas but not restricted to areas of the so‐called default mode network. Hum Brain Mapp 34:3010–3022, 2013. © 2012 Wiley Periodicals, Inc.